Neuroinflammation Following Traumatic Brain Injury: Take It Seriously or Not - Zheng, Rui-zhe; Lee, Kuin-yu; Qi, Zeng-xin; Wang, Zhe; Xu, Ze-yu; Wu, Xue-hai; Mao, Ying (Frontiers in Immunology, 2022)
Traumatic brain injury (TBI) is associated with high mortality and disability, with a substantial socioeconomic burden. With the standardization of the treatment process, there is increasing interest in the role that secondary insult of TBI plays in outcome heterogeneity. The secondary insult is neither detrimental nor beneficial in an absolute sense, among which inflammatory response was a complex cascade of events, and thus can be regarded as a double-edged sword. Therefore, clinicians should take the generation and balance of neuroinflammation following TBI seriously. In this review, we summarize the current human and animal model studies of neuroinflammation and provide a better understanding of the inflammatory response in the different stages of TBI. In particular, advances in neuroinflammation using proteomic and transcriptomic techniques have enabled us to identify a functional specific delineation of immune cell in TBI patients. Based on recent advances in our understanding of immune cell activation, we present the difference between diffuse axonal injury (DAI) and focal brain injury (FBI). In addition, we give figurative profiling of the general paradigm in the pre- and post-injury inflammatory settings employing a bow-tie framework.